2021
DOI: 10.3390/app112110213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Investments in Wind Energy Projects, under Uncertainty. State of the Art Review

Abstract: The use of renewable energy sources, especially wind energy, has been widely developed, mostly during the last decade. The main objective of the present study is to conduct a literature review focused on the evaluation under uncertainty of wind energy investment using the real options approach to find out whether public opposition (NIMBY projects) has been contemplated, and if so, what have been the flexible strategies applied for its intervention. Overall, 97 publications were analyzed, identifying 20 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…For this reason, it is necessary to focus our research efforts on the developments in wind energy projects. It is in this framework that the work of the Murgas et al [20] was developed. In particular, this work is a literature review which evaluates the models and approaches used in the evaluation of investments in wind systems under uncertainty.…”
Section: Power Plants Based On Wind Systemsmentioning
confidence: 99%
“…For this reason, it is necessary to focus our research efforts on the developments in wind energy projects. It is in this framework that the work of the Murgas et al [20] was developed. In particular, this work is a literature review which evaluates the models and approaches used in the evaluation of investments in wind systems under uncertainty.…”
Section: Power Plants Based On Wind Systemsmentioning
confidence: 99%
“…Lastly, a review by Murgas et al [10] evaluates the state-of-the-art in wind energy investment between 2006 and 2020. The authors employed a different classification of the models but identified that the ROA approach was the most popular and that electricity price was the most acknowledged uncertain parameter.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to the authors' best knowledge, no works systematically define and classify E&R uncertainties relevant to RE projects. In addition, as Table 1 shows, the highlighted reviews about uncertainty modeling focus on a single RE technology [10] or problem formulation [5,7,8], do not include E&R parameters [6], or do not detail solution algorithms or methods [9,10]. This review attempts to cover this gap in the following way:…”
Section: Objectivesmentioning
confidence: 99%
“…El uso de las opciones reales tiene relevancia para la evaluación de inversiones en la generación de energía, a partir de la desregulación del sistema de energía y la presencia de mercados de electricidad competitivos, lo que ocasiona una gran incertidumbre, además, de los altos costos iniciales de las inversiones en estas tecnologías y la irreversibilidad de las mismas (Kitzing et al, 2016;Henao et al, 2018;Gazheli y Bergh, 2018;Murgas et al, 2021).…”
Section: Revisión De Literatura Sobre Opciones Realesunclassified
“…En las treinta publicaciones analizadas, con enfoque de opciones reales, se identificaron 29 tipos de incertidumbres, las cuales se categorizaron en ocho grupos: 1) Generación de energía, 2) Medio ambiente, 3) Precios, 4) Costos, 5) Políticas reguladoras, 6) Mercado, 7) Condiciones del viento y 8) Progreso tecnológico, como se muestra en la Tabla 3. Murgas et al (2021) 1. La generación de energía incluye las incertidumbres que afectan el proceso de producción de energía, como el rendimiento del electrolizador y el rendimiento energético.…”
Section: Tipos De Incertidumbres Evaluadas En Las Publicaciones Con U...unclassified